GEOCHEMICAL CHARACTERISTICS OF PIGI AND KARATHODORO MIGMATIZED METASEDIMENTS, GUEVGUELI COMPLEX, MACEDONIA, GREECE - Ζαχαριάδου Σ.; Σολδάτος Τ.; Δημητριάδης Σ. (Bulletin of the Geological Society of Greece, 2004)
Two continental slivers, those of Pigi and Karathodoro (parts of the Stip-Axios unit) are intercalated among members of the Guevgueli ophiolitic complex. These two slivers are closely related with the Late Jurassic basic and acid (expressed mainly by Fanos granite) magmatism ofthat area. A subduction-related volcanic suite intrudes the two continental slivers. Migmatized metasediments constitute the main lithological type of Pigi and Karathodoro. The geochemistry shows that minerals participating in the main decompressional-melting reactions, such as biotite, sillimanite, cordierite, plagioclase and orthoclase, control the differentation of the major elements between mesosomes - diatexites, leucosomes and restites. The refractory behavior of accessory minerals, such as monazite, allanite, zircon, hercynite and ilmenite, control the differentiation of the trace elements. Harker and rare earth element diagrams establish a complementary relationship between restites, leucosomes and mesosomes. In the peraluminous system Ab-Qz-Or leucosomes are projected close to the thermal minimum between 760-800 °C. A main exception is the Platania granite projected within the quartz stability field, probably due to the participation of restitic quartz in its mineralogy. The geochemical results are in good agreement with the pétrographie observations and show that the partial melting was responsible for the formation of Pigi and Karathodoro migmatites